TINDAK TUTUR DIREKTIF GURU DALAM PEMBELAJARAN BAHASA INDONESIA KELAS VIII DI MTS SUNAN KALIJOGO KALIDAWIR TULUNGAGUNG - Mawadah, Sofi Halimah; Jazeri, Mohamad Jazeri (Hasta Wiyata, 2024)
Abstract: The aims of this study were to describe 1) the form of teacher directive speech acts in learning Indonesian in class VIII at MTs Sunan Kalijogo Kalidawir Tulungagung, 2) the function of teacher directive speech acts in learning Indonesian in class VIII at MTs Sunan Kalijogo Kalidawir Tulungagung. This research is a descriptive qualitative research. The source of the data came from the Indonesian class VIII teacher at MTs Sunan Kalijogo Kalidawir Tulungagung. The data collection techniques used were in the form of participatory observation, documentation and free-of-conversation listening techniques. The data were obtained from learning Indonesian on the material structure and linguistic elements of drama texts in class VIII MTs Sunan Kalijogo Kalidawir Tulungagung. The results of the research on teacher directive speech acts in Indonesian Language Learning Class VIII at MTs Sunan Kalijogo Kalidawir Tulungagung found: (1) 6 forms of directive speech acts including requests, questions, prohibitions, giving permission, and advice, (2) the function of directive speech acts The functions found include the functions of asking, pressing, asking, interrogating, instructing, directing, wanting, prohibiting, allowing, agreeing, advising, suggesting, suppressing and advising, instructing and asking, instructing and prohibiting, and the last one suggesting and prohibiting.  Keywords: Directive Speech Acts, Teachers, Indonesian Language Learning. Abstrak: Tujuan penelitian ini adalah untuk mendeskripsikan 1) bentuk tindak tutur direktif guru dalam pembelajaran Bahasa Indonesia kelas VIII di MTs Sunan Kalijogo Kalidawir Tulungagung, 2) fungsi tindak tutur direktif guru dalam pembelajaran Bahasa Indonesia kelas VIII di MTs Sunan Kalijogo Kalidawir Tulungagung. Penelitian ini merupakan penelitian kualitatif deskriptif. Sumber data berasal dari guru Bahasa Indonesia kelas VIII di MTs Sunan Kalijogo Kalidawir Tulungagung. Teknik pengumpulan data yang digunakan berupa observasi partisipatif, dokumentasi dan teknik simak bebas libat cakap. Data diperoleh dari pembelajaran Bahasa Indonesia pada materi struktur dan unsur kebahasaan teks drama di kelas VIII MTs Sunan Kalijogo Kalidawir Tulungagung. Hasil penelitian tindak tutur direktif guru dalam Pembelajaran Bahasa Indonesia Kelas VIII di MTs Sunan Kalijogo Kalidawir Tulungagung ditemukan: (1) 6 bentuk tindak tutur direktif meliputi bentuk permintaan, pertanyaan, perintah larangan, pemberian izin, dan nasihat, (2) fungsi tindak tutur direktif yang ditemukan meliputi fungsi meminta, menekan, bertanya, mengintrogasi, mengintruksi, mengarahkan, menghendaki, melarang, membolehkan, menyetujui, menasihati, menyarankan, menekan dan menasihati, mengintruksi dan  bertanya, mengintruksi dan melarang, dan yang terakhir menyarankan dan melarang. Kata Kunci: Tindak Tutur Direktif, Guru, Pembelajaran Bahasa Indonesia.